1998
DOI: 10.1080/095530098141591
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between ATM protein expression and tumour cell radiosensitivity

Abstract: Variations in the levels of ATM protein are insufficient to explain the differences in cellular radiosensitivity observed in a panel of human malignant glioma cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 27 publications
4
23
0
1
Order By: Relevance
“…A connection also may exist between the levels of DNA-PKcs and ATM. 30 Peng et al 31 demonstrated that the amount or activity of DNA-PKcs influenced ATM expression. In our study, the mRNA levels of ATM, DNA-PKcs, and Ku80 were correlated with one another.…”
Section: Discussionmentioning
confidence: 99%
“…A connection also may exist between the levels of DNA-PKcs and ATM. 30 Peng et al 31 demonstrated that the amount or activity of DNA-PKcs influenced ATM expression. In our study, the mRNA levels of ATM, DNA-PKcs, and Ku80 were correlated with one another.…”
Section: Discussionmentioning
confidence: 99%
“…MO59J cells that are devoid of DNA-PK also exhibit reduced expression of the ataxia telangiectasia mutated (ATM) protein (43). Although the importance of ATM in signaling the DNA damage response to IR is well established (44,45), the levels of ATM do not correlate with radiosensitivity (43).…”
Section: Nhej Status Influences Cisplatin Radiosensitizationmentioning
confidence: 99%
“…Although the importance of ATM in signaling the DNA damage response to IR is well established (44,45), the levels of ATM do not correlate with radiosensitivity (43). If the synergism between IR and cisplatin involves DNA-PK and NHEJ, the inability to signal to this pathway may also be expected to reduce synergism.…”
Section: Nhej Status Influences Cisplatin Radiosensitizationmentioning
confidence: 99%
“…However, a human glioma cell line, M059J, which is characterized by hypersensitivity to radiation and lack of DNA-PKcs protein, has extremely low levels of ATM protein (21). Reverse transcription-PCR failed to detect a difference in ATM mRNA in M059J and a related cell line with normal DNA-PKcs.…”
Section: Introductionmentioning
confidence: 99%